Differentiated Strategy For Performing Reconstructive Plastic Surgery For Diabetic Foot Syndrome - Matmurоtov K.Zh; Ruzmatov P.Yu; Ruzmetov B.A; Saitov D.N (Zien Journals, 2023)
The aim is to improve the results of treatment of patients with wound defects in diabetic foot syndrome due to a differentiated approach of foot surgery
Keywords: Diabetes mellitus; Diabetes Atlas